Diagnosis and treatment of Anaplasma centrale in a domestic cat at Animal Hospital of Hasanuddin University Makassar - Valensie, Vannesa; Monica, Wa Ode Santa; Fatmawati, Dian; Sissiri, Aniza Putri (ARSHI Veterinary Letters, 2023)
Anaplasmosis is a disease caused by obligate gram-negative intracellular bacteria. Anaplasma in cats is generally infected by Anaplasma phagocytophilum, however there are very limited reports of Anaplasma bovis such as Anaplasma marginale and Anaplasma centrale being reported to infect cats. This is the first report of anaplasmosis caused by Anaplasma centrale in cats. The owner brought a one-year-old female domestic cat to the Animal Hospital of Hasanuddin University in Makassar with the condition of not wanting to eat, weak, lethargic, dehydrated, and not defaecating. Diagnosis is carried out through anamnesis, physical examination, clinical examination, and laboratory examination, in the form of haematology and blood smear tests. The results of the examination revealed flea infestation, a blood test identified Anaplasma centrale with characteristics such as the presence of morulae in the middle part of the erythrocytes, and routine blood work showed anaemia which was seen in the MCV parameters increasing and the MCHC values decreased. Treatment consists of administration of antibiotics, anti-inflammatory drugs, and supportive therapy. The cat showed good results, with symptoms starting to disappear and the animal appeared active.